Numerical Simulation of Surface Movement and Deformation Caused by Underground Mining with Complex Stratigraphic Boundary - Liang Wang; Chao He; Songjun Cui; Feifei Wang (Advances in Civil Engineering)
The interface program of finite element software based on surface spline interpolation is developed by using MATLAB software. The controllable 3D surface modeling based on CAD contour is realized. Taking a mine as an example, the method of establishing the 3D numerical calculation model including complex stratum boundary is studied. The influence of underground mining on surface movement and deformation under complex stratum conditions by using the FLAC3D software further was discussed. The research results show that the developed interface program of finite element software can well realize the numerical modeling of complex formation and provide help for subsequent numerical simulation. The calculated subsidence value is in good agreement with the measured value. The values of surface tilt, surface curvature, and surface horizontal deformation are less than the relevant regulations. The mining method of the filling method has no obvious effect on the surface structures. The research results can provide reference for similar numerical simulation.